Modeling and Dynamic Control of a Class of Semibiomimetic Robotic Fish - Shouxu Zhang; Bo Jiang; Xiaoxuan Chen; Jian Liang; Peng Cui; Xinxin Guo (Complexity)
This paper proposes a new robotic fish which avoids the complex mechanical structure and reduces the model complexity comparing to the existing bioinspired robotic fish, giving rise to a semibiomimetic robotic fish. The generalized Lagrange equation is adopted to establish the dynamic model of the robotic fish. The controllability of the system is analyzed, upon which a trajectory tracking control algorithm is designed by using the feedback linearization technique. The simulation results show that the dynamic model adopted in this paper can achieve better control performance.